2013
DOI: 10.1097/ijg.0b013e318264b779
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Mean Deviation Slope and Follow-up Intraocular Pressure in Open-angle Glaucoma Patients

Abstract: Eyes with a faster visual field progression tended to have a higher follow-up IOP in the high-tension group and larger IOP fluctuations in the normal-tension group of OAG patients. We should monitor both the follow-up IOP and fluctuations in IOP to provide a safer and more reliable visual field prognosis for OAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…They found that after 3 years of follow-up, patients with POAG and an IOP SD greater than 2 mm Hg after surgery had a markedly worse mean VF deviation than did patients with an IOP SD of no more than 2 mm Hg. Fukuchi et al 22 similarly found that patients with normal tension glaucoma (NTG) designated as fast progressors based on VF had a higher SD and range in follow-up IOP compared to slow progressors, They found no such correlation for patients with open-angle glaucoma (OAG).…”
Section: Long-term Iop Fluctuationmentioning
confidence: 99%
“…They found that after 3 years of follow-up, patients with POAG and an IOP SD greater than 2 mm Hg after surgery had a markedly worse mean VF deviation than did patients with an IOP SD of no more than 2 mm Hg. Fukuchi et al 22 similarly found that patients with normal tension glaucoma (NTG) designated as fast progressors based on VF had a higher SD and range in follow-up IOP compared to slow progressors, They found no such correlation for patients with open-angle glaucoma (OAG).…”
Section: Long-term Iop Fluctuationmentioning
confidence: 99%
“…Regarding factors after switching, the mean MD slope for 3 years was correlated with the IOP reduction rate at 36 months according to univariate analysis, but not by multivariate analysis (Table 4). Fukuchi et al reported that the MD slope was negatively associated with the mean follow-up IOP in patients with POAG, but this association was not observed in patients with NTG 21. These results suggest that the reduction of IOP after switching to DTFC is the most important factor influencing the progression of visual field loss, but some other potential factors must also be considered.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, we set a threshold for fast/slow progression based on the median of the MD slope [ 15 ] or previously reported values [ 15 , 16 ]. Considering the difference of MD between Octopus (mean defect) and Humphrey perimetry (mean deviation) [ 17 ], 0.22 dB/y and 0.30 dB/y of Octopus may be comparable to the previous MD slope of Humphrey [ 11 , 15 , 16 ]. We found that VCDR and the extent of myopia were associated with fast/slow progression of VF.…”
Section: Discussionmentioning
confidence: 99%
“…The change in MD over time, i.e., the MD slope, was used for evaluating visual progression. Based on previously reported rates of VF progression [ 15 , 16 ], two different threshold values (0.22 dB/y and 0.30 dB/y) were used to distinguish slow progression from fast progression. Initially, the median of the MD slope (0.22 dB/y) was set as the cutoff threshold.…”
Section: Methodsmentioning
confidence: 99%